2021
DOI: 10.1016/j.exger.2021.111321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity interval training combined with traditional strength or power training on functionality and physical fitness in healthy older men: A randomized controlled trial

Abstract: Concurrent training (CT) is an efficient strategy to improve neuromuscular function and cardiorespiratory fitness in older adults, which are factors of pivotal importance for the maintenance of functional capacity with aging. However, there is a lack of evidence about the effectiveness of power training (PT) as an alternative to traditional strength training (TST) during CT. Thus, the aim of the present study was to examine the effect of 16 weeks (twice weekly) TST combined with high intensity interval trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 49 publications
0
19
0
2
Order By: Relevance
“…In regard to physical fitness, lower body strength and aerobic endurance, have been identified as determinant for decrease PA practice in older adults. It has been reported that the process of aging dramatically impacts functional abilities, such as sit-to-stand, gait, and stair climbing abilities ( Reid and Fielding, 2012 ; Müller et al, 2021 ), mainly related to muscle power declines observed during the aging process ( Izquierdo et al, 1999 ; Müller et al, 2021 ). Our results have identified older adults’ lower results in the chair-stand test and lower distance in the aerobic endurance 6-min walk test, as predictors to a decrease in their PA practice over a period of 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to physical fitness, lower body strength and aerobic endurance, have been identified as determinant for decrease PA practice in older adults. It has been reported that the process of aging dramatically impacts functional abilities, such as sit-to-stand, gait, and stair climbing abilities ( Reid and Fielding, 2012 ; Müller et al, 2021 ), mainly related to muscle power declines observed during the aging process ( Izquierdo et al, 1999 ; Müller et al, 2021 ). Our results have identified older adults’ lower results in the chair-stand test and lower distance in the aerobic endurance 6-min walk test, as predictors to a decrease in their PA practice over a period of 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Actualmente, múltiples estudios recientes (Barajas-Galindo, González, Vicente, Ballesteros-Pomara, , 2021; Fougner et al, 2018;Giovanni et al, 2022;León-Olivares, Capella-Peris, Chiva-Bartoll, & Ruiz-Montero, 2019;Müller et al, 2021;Pothier et al, 2021), en la línea de la presente investigación, tratan de averiguar los posibles beneficios que el ejercicio físico puede proporcionar a los adultos-mayores. Específicamente, los programas de entrenamiento concurrente, que, como nos explica Teodoro et al (2019), son programas donde la combinación de fuerza y resistencia aeróbica simultáneamente, son un instrumento ideal para la mejora de la salud mental y física en personas adultas-mayores.…”
Section: Discussionunclassified
“…Un programa de entrenamiento concurrente consiste en combinar el trabajo de dos capacidades físicas: fuerza y resistencia. Se ha evidenciado que el entrenamiento concurrente es una estrategia ideal para minimizar las deficiencias neuromusculares y cardiovasculares que aparecen con el envejecimiento (Teodoro et al, 2019), ya que se trata de un modelo de entrenamiento ideal para el mantenimiento de la capacidad funcional a medida que envejecemos, además de mejorar la función neuromuscular, la capacidad cardiorrespiratoria e índices de composición corporal en adultos-mayores (Müller et al, 2021). Dicho estudio realizó un programa de entrenamiento con personas mayores combinando entrenamiento de fuerza junto con entrenamiento interválico de alta intensidad (siglas en inglés, HIIT) y concluyó que las mejoras fueron similares entre los adultos sanos y los adultos que tenían adaptaciones psicológicas y/o funcionales, por lo que, si un adulto mayor (como es el caso en este estudio) tiene dificultades para realizar algunos ejercicios es esencial adaptar las sesiones a sus capacidades, ya que puede mejorar tanto como un adulto que no necesite adaptaciones.…”
Section: Discussionunclassified
“…This tool provides a reliable assessment of various domains within the studies, with each domain being categorized as having a high, low, or unclear risk of bias [ 25 ]. Among the five manuscripts assessed—Müller et al [ 26 ], Siqueira et al [ 27 ], Wyckelsma et al [ 28 ], Sculthorpe et al [ 29 ], and Bruseghini et al [ 30 ]—each study was found to have a “high risk of bias” in at least one domain [ 25 ] ( Figure 2 ). In the domain of random sequence generation (selection bias), only one study was categorized as having a “low risk of bias” [ 26 ], while another study was marked as “unclear risk” [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the five manuscripts assessed—Müller et al [ 26 ], Siqueira et al [ 27 ], Wyckelsma et al [ 28 ], Sculthorpe et al [ 29 ], and Bruseghini et al [ 30 ]—each study was found to have a “high risk of bias” in at least one domain [ 25 ] ( Figure 2 ). In the domain of random sequence generation (selection bias), only one study was categorized as having a “low risk of bias” [ 26 ], while another study was marked as “unclear risk” [ 30 ]. The remaining articles provided sufficient information to ascertain the adequacy of the randomization sequence generation process, resulting in an overall assessment of “low risk” for this domain.…”
Section: Methodsmentioning
confidence: 99%